ALDH2 Activity Reduces Mitochondrial Oxygen Reserve Capacity in Endothelial Cells and Induces Senescence Properties. (14th November 2018) - Nannelli, G.; Terzuoli, E.; Giorgio, V.; Donnini, S.; Lupetti, P.; Giachetti, A.; Bernardi, P.; Ziche, M.
Abstract : Endothelial cells (ECs) are dynamic cells that turn from growth into senescence, the latter being associated with cellular dysfunction, altered metabolism, and age-related cardiovascular diseases. Aldehyde dehydrogenase 2 (ALDH2) is a mitochondrial enzyme metabolizing acetaldehyde and other toxic aldehydes, such as 4-hydroxynonenal (4-HNE). In conditions in which lipid peroxidation products and reactive oxygen species (ROS) are accumulated, ECs become dysfunctional and significantly contribute to the progression of vascular-dependent diseases. The aim of the present study has been to investigate whether inhibition of ALDH2 alters endothelial functions together with the impairment of bioenergetic functions, accelerating the acquisition of a senescent phenotype. HUVECs transfected with siRNA targeting ALDH2 or treated with daidzin, an ALDH2 inhibitor, were used in this study. We observed an alteration in cell morphology associated with endothelial dysfunctions. Loss of ALDH2 reduced cell proliferation and migration and increased paracellular permeability. To assess bioenergetic function in intact ECs, extracellular flux analysis was carried out to establish oxygen consumption rates (OCR). We observed a decrease in mitochondrial respiration and reserve capacity that coincided with SA- β -Gal accumulation and an increase in p21 and p53 expression in siALDH2 or daidzin-treated HUVECs. Treatment with N-acetyl-L-cysteine (NAC) reduced endothelial dysfunctions mediated by siALDH2, indicating that oxidative stress downstream to siALDH2 plays an instrumental role. Our results highlight that ALDH2 impairment accelerates the acquisition of a premature senescent phenotype, a change likely to be associated with the observed reduction of mitochondrial respiration and reserve capacity.